Ethics and journalistic challenges in the age of artificial intelligence: talking with professionals and experts - Gutiérrez-Caneda, Beatriz; Lindén, Carl-Gustav; Vázquez-Herrero, Jorge (Frontiers in Communication, 2024)
The rapid advancement of artificial intelligence (AI) is substantially transforming media industry, automating mechanical processes and saving time. This set of technologies has been used in different areas like data analysis, automated writing, format transformations, content personalization and fact-checking. AI integration influences work routines, the professional roles of journalists, the relationship with the audience and final products in journalism, offering new opportunities but also arising ethical concerns. These challenges are related to different topics such as data privacy, algorithmic biases, the lack of transparency of used models, and possible job losses, among others. Media outlets and other organizations are creating practical guidelines to help newsrooms navigate AI integration from an ethical perspective, however, these technologies evolves faster than the regulation and the future of journalism is unsure. This paper aims to shed some light through conversations with professionals and researchers in the field, drawing the lines for ethical and responsible AI integration in newsrooms.